Ranibizumab in choroidal neovascularisation associated with ocular sarcoidosis - Konidaris, Vasileios Efstathios (BMJ Publishing Group, 2013)
An 81-year-old Caucasian man with a history of chronic bilateral panuveitis associated with sarcoidosis presented with visual acuity 1.0 LogMAR in the right and 0.5 LogMAR in the left eye. Following fluoroscein angiogram bilateral choroidal neovascular membrane was established. Treatment was initiated with a course of 3 monthly intravitreal injections of ranibizumab 0.5 mg in 0.05 mL bilaterally; oral prednisolone 30 mg/day on tapering doses controlled the ocular inflammation prior to the treatment with intravitreal injections. An additional two intravitreal ranibizumab injections were administered in the right eye. Fibrotic tissue in the posterior pole bilaterally was present on funduscopy following ranibizumab treatment. Visual acuity was LogMAR 1.6 in the right and 1.0 LogMAR in the left eye in 1 year follow-up. This case report summarises the issues of choroidal neovascularisation as a complication secondary to panuveitis associated with sarcoidosis and highlights the treatment of this complication with antivascular endothelial growth factor agents.